Determinación de la eficiencia de remoción de la dbo de agua residual doméstica mediante la utilizanción de un biofiltro de piedra pómez. - Cornejo Soldevilla, Daniela Medalit (2015)
This work was focused on developing a process for the reduction of BOD5 Domestic Wastewater and allowing better water quality. Biofiltration system at laboratory scale in which yeast-like fungi of the species Saccharomyces cerevisiae, attached to a carrier of pumice were used was built. Water was contaminated with a common household waste, regardless of fecal contamination, to simulate a domestic wastewater. To evaluate the efficiency of a biofilter system, it began with the refurbishment and adaptation of the fungus with sugar solution, concentrations were directly measured dissolved oxygen using the Winkler method, pH, total solids. Over a period of 4 days removals were obtained OD =17.41%, pH = 8.97%, ST = 38.49%. To check the efficiency of the Biofilter, the Domestic wastewater without fecal coliforms, it assayed continuous five days per month for a quarter for BOD5, pH, ST. The results obtained have allowed average removal efficiencies BOD5=73.79%, pH = 34.55%, ST = 85.65%. The Biofiltration system studied demonstrated that have high removal efficiencies of organic matter within the optimal range of pH of the sample, reducing the total solids.